News attention to voter fraud in the 2008 and 2012 US elections. (18th May 2015) - Fogarty, Brian J; Curtis, Jessica; Gouzien, Patricia Frances; Kimball, David C; Vorst, Eric C
The nature and frequency of voter fraud figure prominently in many ongoing policy debates about election laws in the United States. Policy makers frequently cite allegations of voter fraud reported in the press during these debates. While recent studies find that voter fraud is a rare event, a substantial segment of the public believes that voter fraud is a rampant problem in the United States. It stands to reason that public beliefs are shaped by news coverage of voter fraud. However, there is very little extant academic research on how the news media, at any level, covers allegations or documented cases of voter fraud. This paper examines local newspaper attention to voter fraud in each of the 50 states during the 2008 and 2012 US elections. The results show that local coverage of voter fraud during the 2012 elections was greatest in presidential swing states and states that passed restrictive voting laws prior to the 2012 election. No evidence that newspaper attention is related to the rate of actual voter fraud cases in each state was found. The findings are consistent with other studies indicating that parties and campaigns sought to place voter fraud on the political agenda in strategically important states to motivate their voting base ahead of the election.